Features of apoptosis and blebbing of the lymphocyte plasma membrane in bronchial asthma - I. A. Solovieva; I. V. Demko; E. A. Sobko; A. Yu. Kraposhina; N. V. Gordeeva; D. A. Anikin; D. A. Anikina (Бюллетень сибирской медицины, 2021)
Given a persistent global trend towards an increase in the number of patients with bronchial asthma (BA) over the past decades, researchers are facing challenges related to a comprehensive study of the pathogenesis of BA. Numerous studies have shown that BA is associated with long-term persistence of leukocytes (lymphocytes, macrophages, and eosinophils) in the bronchial tissues. However, the causes of this phenomenon remain understudied. The article provides an overview of modern research on the mechanisms of disorders of lymphocyte apoptosis in patients with BA.Our study considers the main mechanisms of molecular regulation of  lymphocyte apoptosis, including transcription factors, the Fas/FasL system, and bcl-2/bcl-XL factors. We present the data on the role of reduced lymphocyte apoptosis in the formation of a severe BA phenotype. Taking into account high  prevalence of obesity among patients with BA, we analyzed a few existing articles on the apoptosis of immunocompetent cells in obesity. In addition, the article highlights the key mechanisms of development of lymphocyte plasma membrane blebbing (PMB) with formation of microvesicles, as well as their influence on the course of pathological processes in BA. The authors believe that further in-depth study of apoptosis, lymphocyte  necrosis, and plasma membrane blebbing can help improve the principles of diagnosis and treatment of BA.